ALGORITHMS OF NONPARAMETRIC SYNTHESIS OF DISCRETE ONE-DIMENSIONAL CONTROLLERS - Mallaev А.R., Xusanov S.N., Sevinov J.U. (International Journal of Advanced Science and Technology, 2020)
There are given the algorithms of nonparametric synthesis of discrete one-dimensional controllers in adaptive control systems of technological objects. To build a controllable system and prove its stability, a two-step method is used. It is shown that if the reference solution is found using some optimization method, a recursive controller is obtained, which is almost optimal in the set of linear stationary controllers. It is established that in the case under consideration it is necessary to operate simultaneously with parametric and nonparametric models. In this paper, this problem is solved by using the so-called convolution matrices.